2017
DOI: 10.1007/s13209-017-0168-7
|View full text |Cite
|
Sign up to set email alerts
|

Does trade openness influence the real effective exchange rate? New evidence from panel time-series

Abstract: Using a dataset of 101 countries over the 1960-2011 period, we examine the relationship between the real effective exchange rate (REER), on the one hand, and trade openness, trade balance, the terms of trade, factor productivity, and exchange rate regime, on the other one. We use new econometric estimators that deal with the problems of potential endogeneity and cross-sectional dependence that are present in the data, while also allowing for cross-country heterogeneity in the parameters of interest. The findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…According to Buera et al (2011), nancial frictions induce a misallocation of productive resources across sectors, and consequently larger differences in cross-country productivity in goods sectors compared to the services sectors. Gantman and Dabós (2018) have found that while the effect of productivity on the real exchange rate is positive, it is not always statistically signi cant across all regressions. Nonetheless, Choudhri and Schembri (2010) have shown that as the elasticity of substitution between domestic and foreign goods can vary, the effect of the improvements in traded-goods productivity on the real exchange rate can be positive or negative.…”
Section: Discussion On the Theoretical Effects Of Control Variablesmentioning
confidence: 87%
See 3 more Smart Citations
“…According to Buera et al (2011), nancial frictions induce a misallocation of productive resources across sectors, and consequently larger differences in cross-country productivity in goods sectors compared to the services sectors. Gantman and Dabós (2018) have found that while the effect of productivity on the real exchange rate is positive, it is not always statistically signi cant across all regressions. Nonetheless, Choudhri and Schembri (2010) have shown that as the elasticity of substitution between domestic and foreign goods can vary, the effect of the improvements in traded-goods productivity on the real exchange rate can be positive or negative.…”
Section: Discussion On the Theoretical Effects Of Control Variablesmentioning
confidence: 87%
“…Some works have provided empirical support for the Balassa-Samuelson hypothesis (e.g., Bergin et al, 2006;Buera et al, 2011;Drine and Rault 2003;Gantman and Dabós, 2018;Herrendorf and Valentinyi, 2012). For example, Herrendorf and Valentinyi (2012) have found that the cross-country productivity differences are larger in tradables than in nontradables.…”
Section: Discussion On the Theoretical Effects Of Control Variablesmentioning
confidence: 97%
See 2 more Smart Citations
“…11 See:Bärtschi (1978). 12 See:Kataria and Gupta (2018);Gantman and Dabós (2018);Vogiazas, Alexiou, and Ogan (2019).InternationalJournal of Applied Economics, Finance and Accounting 2021, Vol. 11, No.…”
mentioning
confidence: 99%